2020
DOI: 10.3389/fpsyt.2020.00197
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences Linking Pain-Related Fear and Interoceptive Hypervigilance: Attentional Biases to Conditioned Threat and Safety Signals in a Visceral Pain Model

Abstract: Although the broad role of fear and hypervigilance in conditions of the gut-brain axis like irritable bowel syndrome is supported by converging evidence, the underlying mechanisms remain incompletely understood. Even in healthy individuals, it remains unclear how pain-related fear may contribute to pain-related attentional biases for acute visceral pain. Building on our classical fear conditioning work in a clinically relevant model of visceral pain, we herein elucidated pain-related attentional biases shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“… Courbalay et al (2016) hypothesize a significant mediating role of neuroticism on the level of female fear of severe and medical pain. The increased sensitivity to medical pain in females is also reported by more recent studies such as Heft et al (2007) , Katanec et al (2018) , McLenon and Rogers (2019) , and Labrenz et al (2020) . In addition, female seem to have a significantly higher perceived pain intensity than men, which could also explain these findings ( Diotaiuti et al, 2022b ).…”
Section: Discussionsupporting
confidence: 74%
“… Courbalay et al (2016) hypothesize a significant mediating role of neuroticism on the level of female fear of severe and medical pain. The increased sensitivity to medical pain in females is also reported by more recent studies such as Heft et al (2007) , Katanec et al (2018) , McLenon and Rogers (2019) , and Labrenz et al (2020) . In addition, female seem to have a significantly higher perceived pain intensity than men, which could also explain these findings ( Diotaiuti et al, 2022b ).…”
Section: Discussionsupporting
confidence: 74%
“…However, sex differences in pain-related amygdala neuroplasticity are largely unknown, though one clinical study reported sex differences in resting-state amygdala subnuclei connectivity patterns as a potential explanation for the increased prevalence of conditions of negative affect in women [95]. Even less has been explored about inter-individual and sex differences in fear learning and FE with regard to pain and pain modulation, though a clinical study reported sex differences in pain-related fear conditioning [96]. Ultrasonic vocalizations were previously associated increased neuronal activity in brain regions regulating fear and anxiety, including the amygdala [97], and have been demonstrated to be an effective indicator of emotional status in pain models [20,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…Desde una perspectiva cognitiva, se han estudiado la atención y la hipervigilancia como dos factores importantes para determinar su relación con el dolor (Dimova et al, 2013;Labrenz et al, 2020;Van Damme et al, 2010;Vervoort et al, 2011Vervoort et al, , 2013. Se ha sugerido que la experiencia dolorosa implica una demanda considerable de recursos atencionales (Vervoort et al, 2013).…”
Section: Sesgo Atencional Hipervigilancia Y Dolorunclassified